Effect of Sugarcane Bagasse Ash and Lime Stone Fines on the Mechanical Properties of Concrete - Bheel, N.; Memon, A. S.; Khaskheli, I. A.; Talpur, N. M.; Talpur, S. M.; Khanzada, M. A. (Engineering, Technology & Applied Science Research, 2020)
Cement production releases huge amounts of carbon dioxide having a significant impact on the environment while also having huge energy consumption demands. In addition, the disposal and recovery of natural concrete components can lead to environmental degradation. The use of waste in concrete not only reduces cement production, but it also reduces energy consumption. The aim of this study is to evaluate the properties of fresh and hardened concrete by partially replacing cement with sugarcane bagasse ash (SCBA) and limestone fines (LSF). In this investigation work the cement was replaced with SCBA ash and LSF by 0% (0% SCBA+ 0% LSF), 5% (2.5% SCBA+ 2.5% LSF), 10% (5% SCBA+ 5% LSF), 15% (7.5% SCBA+ 7.5% LSF) and 20% (10% SCBA+ 10% LSF) by weight of cement. In this regard, a total of 60 samples of concrete specimens were made with mix proportion of 1:1.5:3 with 0.56 water-cement ratio. Cube specimens were tested for compressive strength and cylindrical specimens were used for determining splitting tensile strength at 7 and 28 days respectively. The optimum result displayed that the crushing strength and split tensile strength increased by 10.33% and 10.10% while using 5% SCBA+ 5% LSF as a substitute for cement in concrete after the 28th day. The slump value of concrete declined as the content of SCBA and LSF increased.